Henri de Lubac, SJ (1896–1991): Theologian of the Church - Wood, Susan K. (Theology today, 2005)
Henri de Lubac was a leading figure in the theological movement in France in the 1940s known as the “New Theology,” which sought to revitalize theology through a return to Scripture, revival of patristic studies, and liturgical renewal that reaffirmed symbolic elements of liturgical worship. His major accomplishments were a study of patristic and medieval spiritual exegesis, a study of the term corpus mysticum (mystical body), and his reinterpretation of nature and grace in Thomistic theology. Within the categories offered by the “spiritual senses” of medieval exegesis, he integrates a theology of the Eucharist and of the church with a social interpretation of Catholicism.